Probing thermodynamic aspects of electrochemically driven ion-transfer processes across liquid/liquid interfaces: Pure versus diluted redox liquids - Schroder, U; Wadhawan, J; Evans, R; Compton, R; Wood, B; Walton, D; France, R; Marken, F; Page, P; Hayman, C (2002)
The thermodynamical aspects of electrochemically driven ion-transfer processes across liquid/liquid interface were studied. Two conditions were considered: the voltammetry of microdroplets of the pure redox liquids and the voltammetry of the N,N,N',N'-tetraalkylphenylenediamines (TADP) dissolved in nitrobenzene, each deposited as microdroplets at an electrode surface. It was found that the oxidation of the neutral redox liquids leads to the formation of ionic liquid phases, TAPD+X- and TAPD2+X2- (X- = monovalent electrolyte anions).